الاستشھاد الصرفي عند ابن جني في كتابھ الخصائص - Zulkhairi Zulkhairi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2019)
this paper is discussing the tough of Ibnu Jinni on sharf or tashrif in his book Al Khasaish, Ibnu Jinni gave a new paradigm on study of sharf or tashrif, from the traditional point of view based on debate and fanaticism of sects between Kufah and Basrah into more comprehensive studie, among his theories and methodical toughs in his book are the difference between qalam and qaul, ilal arabiyah: between kalamiyah and fiqhiyah,itthirad and suyuz sima’ and qiyas, takhshis ‘ilal, and tadakhul ushul tsulatsiyah and ruba’iyah.